Mexican ENARM: performance comparison of public vs. private medical schools, geographic and socioeconomic regions - Daniela Catherine Hernández-Gálvez; Ernesto Roldán-Valadez (Instituto Nacional de Salud Pública, 2019)
Objectives. This study aimed to compare the performance in the National Assessment for Applicants for Medical Residency (ENARM in spanish) of private versus public medical schools, geographic regions and socioeconomic levels by using three different statistical methods (summary measurements, the rate of change and the area under the receiver operator characteristics [AUROC]). These methods have not been previously used for the ENARM; however, some variations of the summary measurements have been reported in some USA assessments of medical school graduates. Materials and methods. Cross-sectional study based on historical data (2001-2017). We use summary measures and colour-filled map. The statistical analysis included Mann-Whitney U, Kruskal-Wallis, Spearman correlation coefficient (Rs), and linear regression. Results. A total of 113 medical schools were included in our analysis; 60 were public and 53 private. We found difference in the median of total scores for type of schools, MD= 54.07 vs. MD= 57.36, p= 0.011. There were also significant differences among geographic and socioeconomic regions (p<0.05). Conclusions. Differences exist in the total scores and percentage of selected test-takers between type of schools, geographic and socioeconomic regions. Higher scores are prevalent in the Northeast and Norwest regions. Additional research is required to identify factors that contribute to these differences. Unsuspected differences in examination scores can be unveiled using summary measures.